NUMERICAL INVESTIGATION OF NATURAL CONVECTION RADIATION AND MAGNETOHYDRODYNAMIC IN VERTICAL POROUS CYLINDRICAL CHANNEL (Journal of Engineering, 2011)
A numerical study has been carried out to investigate heat transfer by natural convection and radiation under the effect of magnetohydrodynamic (MHD) for steady state axisymmetric twodimensional laminar flow in a vertical cylindrical channel filled with saturated porous media. Heat is generated uniformly along the center of the channel with its vertical surface remain with cooled constant wall temperature and insulated horizontal top and bottom surfaces. The governing equations which used are continuity, momentum and energy equations which are transformed to dimensionless equations. The finite difference approach is used to obtain all the computational results using the MATLAB-7 programming. The parameters affected on the system are Rayleigh number ranging within (102 ≤Ra≤104), radiation parameter (0 ≤Rd≤2) and MHD (Mn) (0 ≤Mn≤2). The results obtained are presented graphically in the form of streamline and isotherm contour plots and the results show that heat transfer enhanced by radiation effect but decrease with the increase of magnetohydrodynamic. A correlation has been set up to give the average Nusselt number variation with Ra, Rd and Mn for which the results are found to be in good agreement with previously published researches which give maximum deviation of 3.73% when compared with the results of (Prasad, 1989).